2012
DOI: 10.1093/bioinformatics/bts310
|View full text |Cite
|
Sign up to set email alerts
|

DoGSiteScorer: a web server for automatic binding site prediction, analysis and druggability assessment

Abstract: rarey@zbh.uni-hamburg.de.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
370
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(375 citation statements)
references
References 11 publications
1
370
0
4
Order By: Relevance
“…3) In silico protein cavity and active site prediction: AADS (Automated active site identification, docking and scoring from IIT Delhi) [19] an automated active site finder, 3DLigandSite [20] for predicting ligand binding sites and DoGSiteScorer [21] a server for automatic binding site prediction, analysis and druggability assessment were used.…”
Section: Materials and Methodmentioning
confidence: 99%
“…3) In silico protein cavity and active site prediction: AADS (Automated active site identification, docking and scoring from IIT Delhi) [19] an automated active site finder, 3DLigandSite [20] for predicting ligand binding sites and DoGSiteScorer [21] a server for automatic binding site prediction, analysis and druggability assessment were used.…”
Section: Materials and Methodmentioning
confidence: 99%
“…The obtained RMSD values indicated that in both cases, the models and the templates had similar folds. Analysis of putative binding pockets using DoGSiteScorer [59] Here, it should be noted that the presence of a binding pocket does not necessarily imply that a target protein is druggable. However, the binding volume is one of the important cavity properties that influence the druggability of a particular target protein, of which most of druggable proteins have volumes of between 500-1000 Å3 [60].…”
Section: Structural Modelingmentioning
confidence: 99%
“…Subsequently, it analyzes the geometric and physicochemical properties of these pockets and estimates druggability with aid of a support vector machine. Thus, the method provides valuable information for target assessment [9].…”
Section: Binding Pocket Predictionmentioning
confidence: 99%